Cross-sectional associations of physical activity intensities and domains with recovery need and burnout risk among Flemish secondary school teachers - Yanni Verhavert; Tom Deliens; Jelle Van Cauwenberg; Juriena de Vries; Peter Clarys; Elke Van Hoof; Evert Zinzen; Kristine De Martelaer (Scientific Reports)
Abstract Secondary schoolteachers face a high recovery need and burnout risk, showing the need for research on how teachers’ recovery need and burnout risk can be reduced/prevented. Physical activity (PA) has shown promise in reducing burnout risk, but the optimal PA intensity and domain remain unclear. This study examined the association of PA intensities across different domains with recovery need and burnout risk in Flemish secondary schoolteachers. A total of 1909 secondary schoolteachers participated in this cross-sectional study conducted in September–October 2019. An online-questionnaire assessed recovery need, burnout dimensions (i.e., emotional exhaustion, depersonalisation, personal accomplishment), and PA intensities (i.e., walking, moderate-intensity PA (MPA), vigorous-intensity PA (VPA)) across five domains: work-related PA, active transport, leisure-time PA, domestic PA and garden PA. Sociodemographic and work-related factors were also questioned. Multiple linear regression models (applied in R) showed that VPA during leisure-time was associated with less recovery need and less emotional exhaustion, whereas moderate-intensity gardening was associated with more recovery need. The association between PA, recovery need and burnout risk depends on the intensity and domain of PA. Secondary schoolteachers may benefit from engaging in leisure-time VPA to reduce/prevent recovery need and burnout symptoms. Longitudinal and experimental studies are needed to establish causal relationships.